2020
DOI: 10.1002/suco.201900374
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flexural performance of concrete reinforced with indented and fibrillated macro polypropylene fibers based on numerical and experimental comparison

Abstract: The fiber/matrix interface in fiber reinforced concrete (FRC) enhances due to the geometry of fiber surface. This work benefits from freedom of fiber engineering due to the availability of fiber production facilities. Non‐indented, indented, flat tape, and fibrillated macro polypropylene fibers were produced. The effect of fiber surface indentation and fibrillation on FRCs flexural performance was investigated. Concrete flexural strength due to the effect of fiber young modulus was found to increases by 94 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The flexural strength increased the maximal 31% for a fiber dosage of 25 kg/m 3 in comparison to the plain concrete. Rostami et al [64] reported that the highest flexural strength was 94% relative to the control sample. Such a large difference may be due to the length of the polypropylene fiber.…”
Section: Discussionmentioning
confidence: 96%
“…The flexural strength increased the maximal 31% for a fiber dosage of 25 kg/m 3 in comparison to the plain concrete. Rostami et al [64] reported that the highest flexural strength was 94% relative to the control sample. Such a large difference may be due to the length of the polypropylene fiber.…”
Section: Discussionmentioning
confidence: 96%
“…As alternative to SFRC, the use of polypropylene macrofibers (PPF) as concrete reinforcement (PPFRC) is experiencing a noticeable increase over the last two decades. [19][20][21] PPFs were reported to present several technical advantages: inert against chloride and chemical attacks to which concrete structures can be subjected; less impact in the concrete workability due to the flexibility of the fiber; lower risk of injuries during manipulation and handling owe also to this flexibility. [22][23][24] In view of that, the use of PPFs is a suitable alternative as a partial or even total substitute of the steel-cage traditionally used in RCPs.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, a unit-cell of the composite is modeled at the meso scale, and the essential parameters are extracted from the meso model. 19,20 Recently, researchers have used Vassiliadis et al's 15 model to create weft-knitted loop geometry at the meso scale. 7,9,[21][22][23] In this model, the geometry of the weft-knitted loop based on the coordinate points of the loop geometry is created in a three-dimensional space.…”
Section: Introductionmentioning
confidence: 99%